Risk factors for child abuse, neglect and exposure to intimate partner violence in early childhood: Findings in a representative cross-sectional sample in Germany. (August 2020) - Liel, Christoph; Ulrich, Susanne M.; Lorenz, Simon; Eickhorst, Andreas; Fluke, John; Walper, Sabine
Abstract: Background: The KiD 0–3 national main study is a cross-sectional study on adversity in early childhood and parental access to support services, conducted as part of a long-term policy program for early intervention services in Germany. Objective: To identify risk factors for child abuse, neglect and exposure to intimate partner violence (IPV) and investigate if parental use of early intervention programs or contact to child welfare services was associated with reported child maltreatment. Participants and setting: 8063 families with infants and toddlers participated in the survey. Parents answered a written questionnaire during mandatory health checks for the child. The sampling was based on a regionally clustered model of pediatricians' practices. Methods: An automatic variable selection process was used to test risk factors and logistic regression models were employed for each outcome. Results: Significant risk factors ( p < 0.05) for child abuse (1.91 %) were child age, IPV and parental stress. Neglect (0.83 %) was associated with couple distress, adverse childhood experiences, young maternal age, cramped housing, and migration history. IPV (2.98 %) was associated with child age, couple distress, depression/anxiety, harsh punishment, adverse childhood experiences, young maternal age, and poverty. Parents were more likely to use selective prevention programs in cases of child abuse and exposure to IPV. Conclusion: Child abuse is mainly associated with proximal risk factors and neglect with distal factors. Exposure to IPV violence is associated with child abuse as well as with an accumulation of adversities. The association between service use and child maltreatment is discussed.